Respuesta :
Hey again!
The solution to the given system is (0, -10)
To solve using elimination, we have to add the equations together, and the "y"s will cancel out, and then solve the equations:
5x - 10 = 6x - 10
Now solve.
Add "10" to both sides:
5x = 6x
Subtract "5x" from both sides
0 = x
Now, we plug in the solved "x" value in an equation to solve for "y".
5(0) + y = -10
y = -10
We now know that the solution to the given system is (0, -10)
Hope this helps! Have an amazing day, and remember, you've got this!!
Step-by-step explanation:
-y - 10 = 6x
5x +y = -10
-6x=10
5x=-10
-x=0
x=0
y=-10-5x or y=-10-6x
y=-10
so (0;-10)